Normative Data for Gait Speed and Height Norm Speed in ≥ 60-Year-Old Men and Women - Kasović, Mario; Štefan, Lovro; Štefan, Andro (Clinical interventions in aging, 2021)
Purpose: To determine normative data for gait speed and height-normalized gait speed in community-dwelling older men and women. Materials and Methods: In this cross-sectional study, we recruited 565 men and women aged ≥60 years old. Age was calculated from the date of birth and further classified into four categories: (1) 60-65 years, (2) 66-70 years, (3) 71-75 years and (4) ≥76 years. Gait speed was assessed by a pressure platform (ZEBRIS, Munich, Germany) in meters per second (m/s). Height and weight were objectively measured. Height-normalized gait speed was calculated by dividing gait speed by height. We created the 20th, 40th, 60th and 80th percentile curves for both outcome measures using Cole's Lambda (L), Mu (M) and Sigma (S) method. Results: Mean gait speed and height-normalized gait speed was 1.24 (standard deviation 0.28) and 0.75 (0.17). Significant age-related decline in gait speed for both sexes was observed (p < 0.001). Being a woman (β = - 0.09, p < 0.001), being older (β = - 0.02, p < 0.001) and having higher body mass index values (β = - 0.02, p < 0.001) were significantly associated with slower gait speed. Conclusion: Gait speed significantly declines with age in both older men and women. Providing normative data can be used in screening and monitoring "slow" walkers to prevent from foot pain and higher risk of falls.
Keywords: Body Height; Walking Speed; Independent Living; Germany; Reference Standards; Female; Age Factors; Gait; ženské pohlaví; průřezové studie; věkové faktory; lidé; Německo; samostatný způsob života; Aged, 80 and over; tělesná výška; Sex Factors; tělesná hmotnost; referenční standardy; Cross-Sectional Studies; rychlost chůze; Male; Aged; sexuální faktory; index tělesné hmotnosti; Body Weight; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Body Mass Index; chůze (způsob); Middle Aged; Humans